Comparison of mini-screw-assisted rapid maxillary expansion in adolescents with different body mass indices: a prospective clinical study - Buyuk Suleyman Kutalmış; Simsek Huseyin; Hatal Sedanur; Sarımehmetoglu Nilge; Odabası Didem (Sciendo, 2022)
The objective of the present study was to compare the dentoskeletal effects of mini-screw-assisted rapid maxillary expansion (RME) in children with different body mass index (BMI) percentiles.